Meta-dynamical adaptive systems and their applications to a fractal algorithm and a biological model - Moulay, Emmanuel; Baguelin, Marc (Physica. D, 2005)
In this article, one defines two models of adaptive systems: the meta- dynamical adaptive system using the notion of Kalman dynamical systems and the adaptive differential equations using the notion of variable dimension spaces. This concept of variable dimension spaces relates the notion of spaces to the notion of dimensions. First, a computational model of the Douady’s Rabbit fractal is obtained by using the meta-dynamical adaptive system concept. Then, we focus on a defense-attack biological model described by our two formalisms.